Prochloraz effects on biomarkers activity in zebraﬁsh early life stages and adults - Domingues, Inês (2018)
Zebraﬁsh early life stages (ELS) assays have been increasingly used to assess the toxicity of chemicals and waste waters, showing a great potential due to the wide variety of endpoints that can be incorporated in the test. Moreover, zebraﬁsh ELS test have been proposed, mainly for ethical reasons, as a surrogate for tests with adults. In this work, the fungicide Prochloraz (PCZ) was used as a chemical model to compare sensitivities of embryos/larvae and adult zebraﬁsh focusing on lethality and biomarkers as endpoints. Effects on embryo development were also assessed. Organization for economic cooperation and development (OECD) guidelines were followed and adapted to include the analyses of the biomarkers cholinesterase, glutathione S-transferase, and lactate dehydrogenase. The acute toxicity of PCZ for zebraﬁsh ELS and adults seemed to be similar with 96h-LC50 values of 8.5 and 4.6 mg/L, respectively. However, biomarkers were only responsive in larvae indicating a higher sensitivity of this life stage at sublethal level. PCZ also proved to be teratogenic: at intermediate concentrations effects on embryo development could be noticed, including spine deformations, edemas, lack of pigmentation, slower heart rate, and complete hatching failure. At the lowest concentrations, the more relevant effects (edemas and abnormal absorption of the yolk sac) were observed after hatching. The measurement of biomarkers in the zebraﬁsh ELS assay seems to a useful tool in the detection of chemical effects showing higher sensitivity than adults. Further research should focus on the link between biomarkers responses in larvae and effects at later life stages of zebraﬁsh.